Orchids of Tropical America : An Introduction and Guide - Meisel, Joe E. (Book collections on Project MUSE., 2014)
"The authors of this introductory text are acknowledged experts on tropical American orchids with decades of combined experience of orchids in both the wild and culture. You could not find a better trio of enthusiasts and specialists to introduce you to the wonderful and occasionally bizarre world of tropical American orchids."--The Foreword by Phillip J. Cribb Orchids of Tropical America is an entertaining, informative, and splendidly illustrated introduction to the orchid family for enthusiasts and newcomers seeking to learn about more than 120 widespread orchid genera. Joe E. Meisel, Ronald S. Kaufmann, and Franco Pupulin bring alive the riot of colors, extraordinary shapes, and varied biology and ecology of the principal orchid genera ranging from Mexico and the Caribbean to Bolivia and Brazil. Orchids, likely the most diverse family of plants on earth, reach their peak diversity in the tropical countries of the Western Hemisphere, including, for example, more than 2,500 species in Brazil and 4,000 in Ecuador. The book also highlights reserves in the American tropics where travelers can enjoy orchids in the wild. Whether you journey abroad to see these unique plants, raise them in your home, or admire them from afar, this book offers fascinating insights into the diversity and natural history of orchids. Beyond the plant and flower descriptions, Orchids of Tropical America is packed with informative stories about the ecology and history of each genus. Pollination ecology is given in detail, with an emphasis on how floral features distinctive to the genus are linked to interaction with pollinators. This book also features information on medicinal and commercial uses, notes on the discoverers, and relevant historical data. The easy-to-use identification system permits quick recognition of the most common orchid groups in Central and South America. Genus descriptions are given in plain language designed for a nonscientific audience but will prove highly useful to advanced botanists as well. Descriptions focus on external morphology, and great care has been taken to ensure the guide is useful in the field without reliance on microscopes or dissections. Equally valuable as a field guide, a desktop reference, or a gift, Orchids of Tropical America will make an excellent addition to any orchid lover's library. Visit the website for this book at www.orchidsoftropicalamerica.com.